Soroprevalência de Toxoplasma gondii em bubalinos e bovinos que compartilham a mesma área no sul do Rio Grande do Sul - Santos, Laura Maria Jorge de Faria (2012)
Toxoplasmosis is a common zoonosis worldwide caused by Toxoplasma gondii, and high infection prevalence in humans and animals. It is usually asymptomatic, however in immunocompromised individuals and in fetuses it may cause severe injury. Wild and domestic felids are the definitive hosts for the parasite, and they shed oocysts in their faeces. Carnivorism, fecal-oral and congenital is the main route of toxoplasmosis transmission. Further studies are needed to investigate the sanity of buffaloes in relation to T. gondii infection, because of the growing demand for buffalo meat and meat products. This work aims to know the prevalence of T. gondii infection in buffaloes and cattle that share the same area in southern Rio Grande do Sul state, and correlate data obtained, including age factor, to identify possible sources of infection. Blood samples were collected by means of jugular venipuncture in 169 buffaloes and 121 beef cattle of different ages, living in a farm in southern Brazil. T. gondii were performed by the indirect fluorescent-antibody (IFA) technique, according to Camargo (1964), using a WAMA Diagnostic® kit. Positive and negative control serum to T. gondii and conjugated Anti-bovine IgG (whole molecule) FITC produced in rabbits, Sigma/F7887 were used. The animals were considered positive from a dilution of 1:64. Significant levels of antibodies to T. gondii were detected in 27.2% of buffaloes and 17.4% of cattle. Statistical difference p≤ 0.05 The presence of cats may also indicate the likelihood of a contaminated environment. Age of animals was significantly associated with seropositivity for toxoplasmosis detected in older buffaloes, due to longer exposure. Buffaloes and cattle are strict herbivores, and high prevalence of T. gondii suggests contamination of the environment by oocysts, featuring horizontal transmission.